ANALISIS HASIL BELAJAR IPS SISWA KELAS IV PADA MASA PANDEMI DI SEKOLAH DASAR NEGERI 59 ENTAKAI II - Yuli Budhiarti (Universitas Tanjungpura, 2023)
The background of this research is that Social Science Education (IPS) is a subject that examines a set of events, facts, concepts and generalizations related to social education issues. education in the school environment not only provides knowledge but also provides values and attitudes and skills.This research method is a qualitative method which is a research method that is descriptive research method, uses analysis, referring to data, utilizing existing theory as supporting materials and producing a theory. this study, collection is throung documention and interviews, the number of studens who were used as samples were 6 people. Based on the research results, it can be concluded that social studies learning